2006
DOI: 10.1177/1049909106292246
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cultural Competence Among Hospice Staff

Abstract: A critical component in making hospice and palliative care services accessible and acceptable to diverse communities is preparation of all providers to enhance cultural competence. This article reports a study designed to test an educational intervention aimed at expanding cultural awareness, sensitivity, and competence with a multi-disciplinary and multilevel team of hospice workers. The purpose of this quasi-experimental, longitudinal, crossover design was to test the effects of an educational intervention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…These results replicated previous studies that established cultural education as a method for increasing cultural competence in health care providers (Beach et al, 2004;Beach et al, 2005;California Endowment, 2003;Lampley et al, 2008;RNAO, 2007;Schim et al, 2006). This study also replicated Choi and Johnson's (2007) finding of no statistically significant difference in results between use of an educational DVD with discussion and use of an education DVD without discussion.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results replicated previous studies that established cultural education as a method for increasing cultural competence in health care providers (Beach et al, 2004;Beach et al, 2005;California Endowment, 2003;Lampley et al, 2008;RNAO, 2007;Schim et al, 2006). This study also replicated Choi and Johnson's (2007) finding of no statistically significant difference in results between use of an educational DVD with discussion and use of an education DVD without discussion.…”
Section: Discussionsupporting
confidence: 94%
“…There was evidence that cultural education increased cultural competence levels of nurses (Beach et al, 2004;Beach et al, 2005;California Endowment, 2003;Lampley et al, 2008;RNAO, 2007;Schim et al, 2006). This study provided additional support for this finding and added to the body of knowledge by specifically addressing the use of DVDs for cultural education with or without discussion guides and facilitated discussion.…”
Section: Implications For Practicesupporting
confidence: 68%
See 1 more Smart Citation
“…Researchers have reported a significant relationship between higher levels of educational attainment and cultural competence among RNs (Braithwaite, 2006;Mahabeer, 2009;Schim, et al, 2006a;Schim, Doorenbos, & Borse, 2006b;Starr & Wallace, 2009). Sealey and colleagues (2006) reported that very few nursing faculty cited formal training in cultural competence, reinforcing the need to further explore the relationship between education/training and cultural competence level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, because the NPCCTN worked with geographically and culturally distinct clinicians, patients, and systems of care, university-based NPCCTN providers and staff completed cultural competence training. 19 The provision of culturally congruent healthcare facilitates strong relationships between academic and tribal providers and AI/AN people.…”
Section: Methodsmentioning
confidence: 99%